Case Report: Meningitis in Postpartum - Pratama, Medio Yoga (Universitas Airlangga, 2024)
Highlight: Meningitis is an infectious disease of the brain membranes and spinal cord. Bacterial meningitis is a severe infection with high mortality and morbidity rates and can be one of the causes of fever in postpartum patients. The most common pathogen that can cause bacterial meningitis is Streptococcus agalactiae (GBS), which causes most of the cases. ABSTRACT Introduction: Meningitis is an infectious disease of the brain membranes and spinal cord. Viruses, bacteria, fungi, parasites, or aseptic actions can all cause meningitis. Bacterial meningitis is a severe infection with high mortality and morbidity rates that can induce fever in postpartum patients. The incidence of invasive Streptococcus agalactiae Group B (SGB) in pregnant women reached 31.58%; the older the pregnant woman, the greater the risk of invasive SGB. Case: The patient came to the emergency room with unconsciousness, fever, and shortness of breath. The patient presented with Ronchi +, neck stiffness +, and GCS E1M1V1. A chest X-ray found cardiomegaly as well as pulmonary edema. A full blood count indicated leukocytosis, increased neutrophils, elevated SGOT and SGPT levels, and lymphocytopenia. The patient was then given antipyretics, anticonvulsants, neurotonics, neurotrophics, diuretics, antihypertensives, and antianginals. Conclusion: In this study, it can be determined whether infection during pregnancy or labor can cause postpartum meningitis. The most common pathogen that can cause bacterial meningitis is Streptococcus agalactiae Group B (SGB), which causes most cases. Early diagnosis of postpartum meningitis is important in order to begin as soon as possible and achieve the best results for the patient's recovery.